SALT-RELATED STRUCTURES IN THE FORELAND FOLD-THRUST BELT OF THE NORTHEASTERN SICHUAN BASIN, SOUTH CHINA - Tang L.; Yu Y.; Jin W.; Li R.; Guo T.; Zhou Y. (My University, 2007)
Three tectono-stratigraphic sequences can be divided in the northeaster Sichuan basin according to the Mid- and Lower-Triassic salty and gypsum beds. The sub-salt tectono-stratigraphic sequence, dominated by a marine-facies sedimentary carbonate sequence, is composed of the Sinian and Lower-Triassic Feixianguan Formation. Assemblage of the salt sequence and structure includes the Upper-Triassic Jialingjiang Formation and Mid-Triassic Leikoupou Formation and is characterized by saliniferous marine carbonate measures. The supra-salt sequence is composed of continental clastic rocks belonging to the Upper-Triassic Xujiahe Formation, Jurassic and Cretaceous. A series of specific structural styles, such as intense deformed belt of basement-revolved imbricated thrusts, superimposed deformed belt associated with the basement-revolved and salt detachment, buried salt-related detachment zone, duplex, triangle pile structure and pop-up, are developed in the northeastern Sichuan basin. Relatively thin salt beds in this area may act as a large-scale, decollement zone which controls the structural deformation of northeastern Sichuan basin. The deformation mechanisms of north eastern Sichuan basin have a bearing upon the regional compression and shortening, plastic flow and detachment, tectonic upwelling and erosion, gravitational sliding and spreading. The tectonic deformation related to the Triassic in the northeastern Sichuan basin may control the pattern of oil/gas traps, which are favorable to the accumulation and reservation of hydrocarbon.
Keywords: CARBONATE MEASURES; DEFORMATION MECHANISMS; FORELAND FOLD-THRUST BELT; NORTHEASTERN SICHUAN BASIN; SALT-RELATED STRUCTURE; Mesozoic::Triassic; Мезозой::Триасовая